Efektivitas Pembelajaran Dalam Jaringan (Daring) Selama Pandemi Covid-19 Di Kabupaten Jombang - Hanum, Fauziah; Yanuarita, Heylen Amildha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This research was conducted to determine the effectiveness of online learning for students in Jombang Regency, East Java during the pandemic period due to COVID-19. The method used in this research is descriptive qualitative method with the addition of a simple literature review review. This technique is used to get a detailed and comprehensive description and explanation of existing data. Where data retrieval was carried out with a more in-depth approach to the subject, assisted by various pre-existing literature reviews. The results indicate that the online learning process during the pandemic is still not optimal. This is due to the many obstacles experienced, such as a lack of infrastructure such as internet devices and networks, as well as a lack of digital media literacy in the community.